Characterization by Confocal Laser Scanning Microscopy of the Phase Composition at Interfaces in Thick Films of Polymer Blends. (30th March 2014) - Lattante, Sandro; Perulli, Andrea; Anni, Marco
Abstract : Confocal Laser Scanning Microscopy (CLSM) has been used as a fast, user-friendly, and noninvasive tool for characterizing the phase composition differences at the substrate and air interfaces in thick films of polymer blends. A clearly different phase composition at the blend/glass interface and at the blend/air interface has been detected. We show that PCBM preferentially accumulates at the glass/blend interface, while P3HT preferentially accumulates at the blend/air interface, by comparing the integrated signal intensity of the luminescence coming from both interfaces. Our results demonstrate that CLSM can be used conveniently for the fast identification of a preferential phase segregation at interfaces in polymer blends. This is useful in the research field on devices (like sensors or planar waveguides) that are based on very thick layers (thickness higher than 1  μ m).